Novel biosurfactant assisted biodegradation of polystyrene by Actinomycetes and its chemical understanding - Sakpal, Amrapali; Haq, Nazrul; Dasgupta, Santanu; Alanazi, Fars; Alsarra, Ibrahim A.; Alam, Mahboob; Dastager, Syed G. (Polymer Degradation and Stability, 2026)
The current study highlights the effective biodegradation of polystyrene by two actinobacterial strains, Glutamicibacter sp. K-1 and Rhodococcus sp. BG-30. FT-IR, Raman spectroscopy, and GPC data showed the degradation pattern of polystyrene. Additionally, GC-MS analysis showed that strain K-1 produced a variety of degradation by-products, including alkanes, 2,4-Di-ter-butyl phenol, 2-propenoic acid, tridecyl ester, and dibutyl phthalate, while strain BG-30 produced a greater amount of alkenes, phthalic acid, and isobutyl octyl esters. GPC detected a drop in polystyrene's average molecular weight (Mn), which suggests chain scission of the polymer. Changes in polystyrene's roughness and other morphological properties were shown by AFM and FE-SEM. The effects of a conventional rhamnolipid and a novel thermostable biosurfactant fatty alkene (0.1 % each) on the breakdown of polystyrene were examined. Strain K-1 and BG-30 resulted in increasing the degradation of polystyrene to 12 % (w/w) and 16 % (w/w), respectively in the presence of fatty alkene biosurfactant, there was 10 % (w/w) and 8 % (w/w), degradation in presence of rhamnolipid. To the best of our knowledge, degradation of polystyrene by Glutamicibacter sp. has been reported as a newly identified strain and use of a novel biosurfactant together revealed their potential in biodegradation of plastic to mitigate the plastic pollution using microbial resources.
Keywords: Biodegradation; Fatty alkene biosurfactant; Glutamicibacter sp.; Polystyrene; Rhamnolipid; Rhodococcus sp.